Lutophila gen. nov., a new diatom genus from the hottest place on Earth, Lut Desert, Iran - Kheiri, Somayyeh; Edlund, Mark B.; Spaulding, Sarah; Nadir Solak, Cüneyt; Sabouri, Jafar; Izadi, Bahman; Peszek, Łukasz (Phytotaxa, 2024)
The Lut Desert is one of the world’s driest and hottest large deserts. This large basin has shallow groundwater pools that have been studied little for microbial flora, especially diatoms, and the present study is the second attempt. We report a new genus with one new species and the related morphotypes. The genus Lutophila and its type species L. iranica is found in hypersaline pools and a saline river in the Central Lut Desert depression, an area known as the hottest spot in the world. The morphology, systematic position, distribution, and ecological conditions of the new species and its morphotypes are discussed. The new genus Lutophila has a linear-lanceolate, symmetric outline with broadly rounded apices and two kinds of areolae, one on the valve face and one on the valve mantle; these characters resemble those shared by the diatom genera Krasskella, Biremis, Chamaepinnularia and Oestrupia. Lutophila iranica exhibits two morphotypes with similar outline; however, L. iranica morphotype 2 is wider than the L. iranica morphotype 1 and has a more distinctive central area.